Analysis of competitiveness through intellectual capital in companies listed on the Mexican Stock Exchange - Campa Dominguez, Isaid; Béjar Tinoco, Víctor; Madrigal Moreno, Flor; Madrigal Moreno, Salvador (Revista Venezolana de Gerencia, 2024)
The objective of this research is to analyze intellectual capital as a tool for creating value in Mexican companies that seek to be more competitive in the market, analyzing their disclosure of intangible matters, as well as the factors that motivate said disclosure. To carry out the analysis, companies from different sectors that are listed on the Mexican Stock Exchange (BMV) were selected. The selection was based on criteria of representativeness and availability of detailed financial and operational data. A quantitative methodology was used, applying multiple regression techniques and factor analysis to measure the influence of intellectual capital variables on competitiveness. The analysis revealed that intellectual capital has a significant impact on the competitiveness of companies listed on the BMV. These findings indicate that a comprehensive and balanced management of the different components of intellectual capital is crucial to improve business competitiveness. The study concludes that companies listed on the BMV should focus on strengthening their intellectual capital to improve their competitiveness to maximize their performance in the market.